2016
DOI: 10.1093/mnras/stw422
|View full text |Cite
|
Sign up to set email alerts
|

Deep spectroscopy of nearby galaxy clusters – I. Spectroscopic luminosity function of Abell 85

Abstract: We present a new deep spectroscopic catalogue for Abell 85, within 3.0 × 2.6 Mpc 2 and down to M r ∼ M * r +6. Using the Visible Multi-Object Spectrograph at the Very Large Telescope and the AutoFiber 2 at the William Herschel Telescope, we obtained almost 1430 new redshifts for galaxies with m r ≤ 21 mag and µ e,r ≤ 24 mag arcsec −2 . These redshifts, together with SDSS-DR6 and NED spectroscopic information, result in 460 confirmed cluster members. This data set allows the study of the luminosity function (LF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 72 publications
6
60
1
Order By: Relevance
“…The large uncertainty in α results from the large observational errors in the LF. This slope is less steep than others from massive clusters (α ∼ −1.5; Agulli et al 2014;Agulli et al 2016) or the field (Blanton et al 2005). Nevertheless, the slope is similar within the uncertainties with the LF in groups of galaxies (α ∼ −1.16; Zandivarez & Martínez 2011) or some dynamically young massive clusters (α ∼ −1.13; Agulli et al 2017).…”
Section: The Spectroscopic Galaxy Luminosity Functionsupporting
confidence: 68%
See 1 more Smart Citation
“…The large uncertainty in α results from the large observational errors in the LF. This slope is less steep than others from massive clusters (α ∼ −1.5; Agulli et al 2014;Agulli et al 2016) or the field (Blanton et al 2005). Nevertheless, the slope is similar within the uncertainties with the LF in groups of galaxies (α ∼ −1.16; Zandivarez & Martínez 2011) or some dynamically young massive clusters (α ∼ −1.13; Agulli et al 2017).…”
Section: The Spectroscopic Galaxy Luminosity Functionsupporting
confidence: 68%
“…A total of 129 spectroscopic targets were selected and located in two AF2 fiber configurations. We obtained low-resolution spectra (R = 280 and grism R158B) in three exposures of 1800s per pointing, with the spectra reaching S /N > 5 for a secure redshift determination (see e.g., Agulli et al 2016). We also selected targets with g−r < 1.1 and 19.5 < m r < 21.0 to be observed with the OSIRIS@GTC instrument.…”
Section: The Data For Rxj0752436+455653mentioning
confidence: 99%
“…Ferrarese et al (2016) show that the Virgo LF (and also SMF) is significantly shallower than the expected distribution from ΛCDM (a~-1.9, e.g., Springel et al 2008). Other spectroscopic LFs including A85 (Agulli et al 2016) and A2199 (Rines & Geller 2008) are also less steep than the subhalo mass distributions derived from simulations. However, the complexity of the transformation from subhalo mass to luminosity is nontrivial and thus these comparisons are hard to interpret.…”
Section: Comparison Of the Smfs With Simulationsmentioning
confidence: 73%
“…Statistical studies of spectroscopically confirmed cluster members control for some observational biases. Nonetheless, there are few studies that explore the LF (Rines & Geller 2008;Agulli et al 2014Agulli et al , 2016 or the SMF (Ferrarese et al 2016) of spectroscopically identified members. In contrast, there are many studies based on photometrically determined membership (e.g., Barkhouse et al 2007;Moretti et al 2015;Lan et al 2016;Lee & Jang 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The dip magnitude of Abell 2744 is similar to the values in the previous studies, M r ≈ −18 ± 1 mag. It has been suggested that the presence of this gap can be explained by the efficiency of merging of intermediate luminosity galaxies depending on the galaxy density (Miles et al 2004;Mercurio et al 2006;Agulli et al 2016;Lee et al 2016). Low density regions like the galaxy groups, poor galaxy clusters, or outskirt of rich galaxy clusters have a higher efficiency of galaxy merging than that of the high density regions, because they have lower velocity dispersion.…”
Section: Discussion 41 Comparison Of the Galaxy Lfsmentioning
confidence: 99%